Novel polymer‐ceramic composites for protection against ballistic fragments. Issue 2 (27th December 2012) - Naebe, Minoo; Sandlin, James; Crouch, Ian; Fox, Bronwyn
Abstract For the first time, internally reinforced aggregate polymer ceramic composites were evaluated against fragment simulating projectiles (FSPs) of various calibers to investigate their ballistic impact response. Samples were prepared by mechanically mixing B4C and cBN over a range of ratios and combinations with either thermosetting phenolic or epoxy resin and aramid pulp. Dry mixtures were then molded in a closed die using a heated platen press. The resulting tiles were then mounted as "strike faces" to an aramid backing material using an epoxy resin. Backed targets were tested in a fully instrumented firing range against 5.56 mm FSPs to test ballistic limit. A further series of tests using 7.62, 12.5, and 20 mm FSPs was conducted to examine round deformation across a range of fragments calibers. Round deformations were measured after impact and plotted against shot velocity. It was found that the polymer ceramic composite materials were effective round deformers and, like sintered ceramic strike faces, demonstrated improved ballistic performance at an equivalent areal density and impressive multihit capability. POLYM. COMPOS., 2012. © 2013 Society of Plastics Engineers